2021
DOI: 10.1097/meg.0000000000002185
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer, inflammatory bowel disease and polyautoimmunity in a 17-year-old boy: CTLA-4 deficiency successfully treated with Abatacept

Abstract: Gut involvement is frequent in immunologic disorders, especially with inflammatory manifestations but also with cancer. In the last years, advances in functional and genetic testing have improved the diagnostic and therapeutic approach to immune dysregulation syndromes. CTLA-4 deficiency is a rare disease with variable phenotype, ranging from absence of symptoms to severe multisystem manifestations and complications. We describe a rare case of CTLA-4 deficiency in a boy with gastric cancer, very early onset in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 459 people with PI and COVID-19 are described from 54 of the 68 studies [ 12 , 13 , 16 , [18] , [19] , [20] , [21] , 24 , 26 , 27 , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] ] (Table 2). These cases came from case reports as well as cohort studies with information available for individual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Abatacept was well-tolerated, but allowed for only a mild reduction of glucocorticoids dosage, which was not enough to change the course of her disease, with death following two years after the start of treatment. Recent case reports described the effective use of abatacept to treat pediatric patients with either autoimmune or autoinflammatory manifestations and an underlying CTLA4 deficiency [13][14][15]. Another case, a girl with autoimmune thyroiditis, gastritis, oral ulcerations and mucosal candidiasis, with positive antinuclear and anti-DNA antibodies, was treated with hydroxychloroquine based on a diagnosis of Systemic Lupus Erythematosus, with scarce control of symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed characteristics of the included studies are shown in Additional file 2 : Table S3. There were 73 case report [ 4 6 , 8 , 9 , 25 32 , 37 39 , 44 , 45 , 49 , 51 , 53 60 , 67 69 , 72 , 76 79 , 82 84 , 86 88 , 90 , 91 , 93 , 94 , 96 , 99 107 , 109 114 , 116 , 119 123 , 126 , 127 , 129 – 131 ], 38 cohort [ 7 , 10 , 19 , 33 – 36 , 40 43 , 46 48 , 50 , 52 , 61 66 , 70 , 71 , 73 , 74 , 80 , 81 , 92 , 95 , 97 , 98 , 108 , 117 , 118 , 124 , 125 , 132 ], 4...…”
Section: Resultsmentioning
confidence: 99%
“…Only six studies were made within multi-countries (n = 6) [ 10 , 33 , 35 , 51 , 95 , 132 ]. The majority of the studies were single centre [ 4 6 , 8 , 9 , 19 , 25 32 , 34 , 37 39 , 41 , 43 47 , 49 , 50 , 52 60 , 62 , 64 , 66 69 , 71 , 72 , 75 80 , 82 84 , 86 90 , 93 , 94 , 96 , 98 – 117 , 119 131 ] and only 23 studies were multi-centre [ 7 , 10 , 33 , 35 , 36 , 40 , 42 , 48 , 51 , 61 , 63 , 65 , 70 , 73 , 74 , 81 , 85 , 91 , 92 , 95 , 97 , 118 , 132 ]. Among all included studies in our systematic review, only one study reported on the other potential modifiers in immunity-related pathways for all diagnosed IEIs in children who were infected with SARS-CoV-2 (n = 1, 0.9%) […”
Section: Resultsmentioning
confidence: 99%